TEACHING READING COMPREHENSION IN NARRATIVE TEXT BY USING CHARACTER MAP STRATEGY TO THE EIGHTH GRADE STUDENTS OF SMP AZZAWIYAH TANJUNG BATU - riska amalia (State Islamic University of Raden Fatah Palembang, South Sumatra, Indonesia, 2017)
The objectives of this study were to find out whether or not there was a significant improvement before and after the treatment on the eighth grade students’ reading comprehension scores of SMP Azzawiyah Tanjung Batu by using Character Map Strategy and to find out whether or not there is a significant difference on the eighth grade students who were taught by using Character Map Strategy and those who were not. In this study, the researcher used Quasi Experimental Design using pretest-posttest nonequivalent groups design. There were 72 students taken as sample. Each class consisted of 36 students from VIIIa as experimental group and class VIIIb as control group. In collecting the data, test was used. The test was given twice to both experimental and control groups, as a pretest and posttest. To verify the hypotheses, the data of pretest and posttest were analyzed by using paired sample t-test and independent sample t-test on SPSS program. The findings showed that the p-output from paired sample t-test (Sig2-tailed) was 0.000 which was lower than 0.05 and t-value 11.931 was higher than t-table with df35= (2.0301). The result of p-output from independent sample t-test was 0.003 which was lower than 0.05 and the t-value 3.062 was higher than t-table with df=70 (1.9944). It means that teaching reading comprehension in narrative text by using Character Map Strategy had significant effect on the students’ reading comprehension scores.